Estudo do crescimento e composição corporal de linhagens de codornas de corte e postura - Grieser, Daiane de Oliveira (2012)
The experiments was carried out to determine the performance, carcass yield and cuts, growth parameters of live weight, body chemical components of organs and carcass parts of males and females of meat-type quails strain (Coturnix coturnix sp) and two laying quails strains (Coturnix eoturnix japonica), called yellow and red. It has been used 1.350 quails, from 1 to 42 days of age, created on shed, housed in boxes. The design was completely randomized, with three treatments (each treatment corresponds to one quails strain) and five replications with 80 quails for meat-type quails strain, 90 to the yellow strain and 100 to the red strain. The birds were fed ad libituim with diets formulated according to requirements for each age phase. It has been evaluated the weekly performance, the careass yield and cuts at 35 and 42 days old oftwo quails per replication (a male and a female). In these evaluations, the meat-type strain gave greater weight, weight average gain, feed conversion, accumulated body biomass of 1 to 14 days of age, housing income to 35 days and breast yield to 35 and 42 days of age, showing good suitability for meat production. Among the laying quails strains, the red was better than the yellow in weight gain, feed conversion and wing income to 42 days of age. The effect of sex was observed to the yield of wing and dorsum to 35 days of age and breast to 42 days. It is concluded that the laying and meat-type quails presented greater accumulated body biomass and better feed gain ratio from 1 to 14 days old demonstrating greater efficiency of growth during this period. There has been more development of the meat-type strain with improved carcass yield to 35 days old. In the second experiment was assessed weekly individual growth of quail and the deposition by body chemistry Gompertz equation, and growth rates determined by equations derived. Females of the three strains showed greater body growth rates compared to the males of the same strains, accelerated growth occurring up to 14 days of age for males and 21 days for females. Among the laying strains, the greatest potential in depositing presented red protein and water on the carcass, and was earlier in the deposition of bodily nutrients than the yellow. It is concluded that it was possible to estimate the parameters of the Gompertz equation for body weight and body composition of protein, water and ash of the meat-type and laying quails, when evaluated up to 42 days of age. The strains studied showed different growths live weight and depositions of nutrients in the body, but the females were later and it showed higher growth and deposition of nutrients than males. In the third experiment was assessed weekly growth of organs and parts of the carcass of two quail by repetition (a male and a female) through the Gompertz equation, and growth rates determined by equations derived. The meat-type strain presented greater growth of organs and parts of the carcass reviewed here. Females of the three strains showed greater weight to maturity to the viscera, however the earliest were males. As for the parts of the carcass, females have greater potential for crop growth and breast, wings and breast, yellow dorsum and red for all parties assessed, if cornpared with males of the same strain. It is concluded that it was possible to estimate the parameters of the Gompertz eql and laying. The strains studied showed different values o growth for these variables, It was observe increase growth of organs and parts of the carcass to the meat-type strain and between the sexes, the females stood in relation to males.